2023
DOI: 10.1186/s12903-023-02996-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Er:YAG laser irradiation on the outcomes of alveolar ridge preservation at the infected molar sites: a randomized controlled trial

Abstract: Background The purpose of this study was to investigate the socket healing outcome after alveolar ridge preservation at infected molar sites using an erbium-doped yttrium aluminium garnet (Er:YAG) laser. Methods Eighteen patients who needed molar extraction and exhibited signs of infection were included and allocated into either the laser group or the control group. Er:YAG laser irradiation for degranulation and disinfection was performed with alve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The article [44] describes a method whose purpose is to analyze the effectiveness of laser in healing infected areas of the tooth socket. Histologically, it was revealed that the laser stimulated osteogenesis due to the expression of osteocalcin.…”
Section: Use Of Laser For Socket Preservationmentioning
confidence: 99%
“…The article [44] describes a method whose purpose is to analyze the effectiveness of laser in healing infected areas of the tooth socket. Histologically, it was revealed that the laser stimulated osteogenesis due to the expression of osteocalcin.…”
Section: Use Of Laser For Socket Preservationmentioning
confidence: 99%